La hipertextualitat i la intermedialitat en Odissea, el viatge de Ningú (2017), d'Elies Monxolí. - CANO MATEU, J. ÀNGEL; HERNÀNDEZ I GARCIA, XAVIER (Scripta)
Homer's Odyssey is a major pillar of the Western literary canon that has resulted in hundreds of versions, translations, or rewritings, both from a literary point of view and from a musical or artistic point of view. In fact, as Gérard Genette (1982) points out, it is one of the most commonly used hypotexts, which have inspired great works such as the Aeneid and James Joyce's Ulysses. Also Odissea, el viatge de Ningú, by Elies Monxolí: a new reading of the Homeric story based on the translations of Carles Riba and Joan Francesc Mira, that incorporates references to Ausiàs Marc, Dante Alighieri, Salvador Espriu and Vicent Andrés Estellés, among others. To this hypertextual richness is added the music, which is adapted to the text and, at the same time, integrates allusions to Lluís Llach and Raimon. The collages of Pere Salinas complete this interdisciplinary creation that amalgamates literature, music and plastic art. The aim of this article is to analyse, on the one hand, the hypertextuality of this work, following Genette, and, on the other, the intermediality relations between the different artistic disciplines that conform it, following the typologies developed by Werner Wolf (1999).